Assessing and treating complex mental health needs among homeless youth in a shelter-based clinic - Dominika A. Winiarski; Anne K. Rufa; Dawn T. Bounds; Angela C. Glover; Kristin A. Hill; Niranjan S. Karnik (BMC, 2020)
Abstract Background Rates of homelessness have been increasing in recent years, thereby necessitating a more direct approach to treating this complex social problem. Homeless youth have disproportionately high rates of untreated mental health problems and are therefore particularly vulnerable to the effects of homelessness during the transition period from adolescence to adulthood. Methods The study team developed a shelter-based clinic and collected clinical measures on youth who attended this clinic from October 2016 through June 2018. Results Youth attended an average number of three sessions, but there was a significant drop in follow-up after the first (intake) appointment. Depression, anger, and adjustment disorder emerged as the most common presenting mental health concerns identified by clinicians in the intake appointment, and trauma was identified as a significant complaint for those youth who returned for a second session. Conclusion Mental health care is needed in this population, but future studies should explore alternative approaches to retaining homeless youth in treatment and in designing targeted trauma-informed interventions.